Non-Vitamin K Oral Anticoagulant After Transcatheter Aortic Valve Replacement: A Systematic Review and Meta-Analysis - Li, Dongxu; Ma, Xiaofang; Zhou, Xu; Qian, Yongjun (Frontiers in Pharmacology, 2022)
Objective: We aimed to compare non–vitamin K oral anticoagulants (NOACs) with a traditional antithrombotic such as vitamin K antagonist (VKA) and antiplatelet agents in patients after transcatheter aortic valve replacement (TAVR). Methods: We conducted a search in PubMed, EMBASE, and the Cochrane Library until November 2021 for studies involving comparisons of any type of NOACs, including dabigatran, apixaban, rivaroxaban, and edoxaban, with VKA or antiplatelet agents after TAVR. A comparison of NOACs versus VKA was performed in patients with an indication for oral anticoagulation. In addition, we compared NOACs versus antiplatelet in patients without such indication. We calculated the hazard ratios (HRs) with 95% confidence intervals (CIs) to determine long-term outcomes. The primary outcome was a combined endpoint consisting of all-cause mortality, stroke, major bleeding, or any related clinical adverse events. Secondary outcomes were all-cause mortality, major bleeding, and stroke, respectively. Results: A total of 10 studies including 10,563 patients after TAVR were included in this meta-analysis. There were no significant differences in any of the long-term outcomes between the NOAC and VKA groups. Although there were no significant differences in the combined endpoint, major bleeding, or stroke, a significant difference was observed in all-cause mortality (HR 1.74, 95% CI 1.25–2.43, p = 0.001) between the NOAC and antiplatelet groups. Conclusion: For patients with an indication for oral anticoagulation after TAVR, NOACs seem to be associated with noninferior outcomes compared with VKA therapy. However, for patients without an indication for oral anticoagulation, NOACs appear to be associated with a higher risk of all-cause death as compared with antiplatelet treatment. Registration number: CRD42020155122.